The Effect of Severe Intraventricular Hemorrhage on the Biorhythms of Feeding in Premature Infants - Ira H. Gewolb; Babatunde T. Sobowale; Frank L. Vice; Abhijit Patwardhan; Nino Solomonia; Nino Solomonia; Eric W. Reynolds; Eric W. Reynolds (Frontiers Media S.A., 2021)
Background: Suck-swallow rhythmicity and the integration of breathing into infant feeding are developmentally regulated. Neurological injury and breathing abnormalities can both impact feeding in preterm infants.Objective: To determine the effects of neurologic injury independent of effects of disordered breathing on feeding biorhythms in premature infants.Methods: Low-risk preterm infants (LRP), infants with Grade 3-4 Intraventricular Hemorrhage (IVH), those with bronchopulmonary dysplasia (BPD), and those with both BPD and IVH (BPD+IVH) were identified. Forty-seven infants, 32-42 weeks Postmenstrual Age (PMA) were evaluated on one or more occasions (131 studies). Of these, 39 infants (81 studies) were performed at >35 weeks PMA. Coefficient of variation (COV) (=standard deviation of the inter-event (e.g., suck-suck, swallow-breath, etc.) interval divided by the mean of the interval) was used to quantify rhythmic stability.Results: To adjust for PMA, only those infants >35-42 weeks were compared. Suck-suck COV was significantly lower (more rhythmically stable) in the LRP group [COV = 0.274 ± 0.051 (S.D.)] compared to all other groups (BPD = 0.325 ± 0.066; IVH = 0.342 ± 0.072; BPD + IVH = 0.314 ± 0.069; all p < 0.05). Similarly, suck-swallow COV was significantly lower in LRP babies (0.360 ± 0.066) compared to the BPD group (0.475 ± 0.113) and the IVH cohort (0.428 ± 0.075) (p < 0.05). The BPD+IVH group (0.424 ± 0.109), while higher, was not quite statistically significant.Conclusions: Severe IVH negatively impacts suck-suck and suck-swallow rhythms. The independent effect of neurological injury in the form of IVH on feeding rhythms suggests that quantitative analysis of feeding may reflect and predict neurological sequelae.